Grabbing lightning : building a capability for breakthrough innovation - O'Connor, Gina Colarelli (Jossey-Bass, 2008)
Grabbing Lightning To stay competitive in today's global marketplace, companies need to learn how to harness and sustain innovation rather than relying on the unexpected. Established companies are clamoring for breakthrough innovation, but are often hamstrung by the highly reliable, repeatable processes of their management systems. Based on years of research, Grabbing Lightning shows how twelve companies have tried to develop a capability for sustainable breakthrough innovation and outlines best practices for your organization. The authors show how the management system for innovation is different from the traditional one in that it allows-and even encourages-mistakes and failures in order to promote learning. Grabbing Lightning outlines the three building blocks of breakthrough innovation and shows what it takes to become an organization that values the breakthrough innovation management system. In Grabbing Lightning, the authors: Explore the discovery competency and show how it differs from R & D Examine the incubation competency and reveal how incubation can greatly enhance an organization's options for new business creation Focus on the acceleration competency and address the activities it involves and approaches companies are taking toward it The book also explores the challenges organizations can expect to face once a breakthrough innovation capability is initiated and offers advice for establishing innovation as a sustainable business function in organizations. Grabbing Lightning is a hands-on resource for all established organizations who want to make breakthrough innovation the norm rather than the exception.